Sandball genesis from raindrops - Bertil Trottet; Daisuke Noto; Douglas J. Jerolmack; Hugo N. Ulloa (Proceedings of the National Academy of Sciences, 2025)
In the water cycle, erosion begins with the entrainment of soil by raindrops. The discrete, discontinuous, and three-phase nature of raindrop erosion—at the boundary of fluid and granular mechanics—makes this problem particularly challenging, compared to better-studied sediment transport by river and wind currents. Past research has emphasized particle entrainment by raindrop splash at impact. Here, we report lab and field observations, that uncover a surprisingly rich and efficient postimpact phase. Raindrops impacting a dry, sloping, granular bed spontaneously form “sandballs;” drops of dense suspensions that can grow in mass to a jammed state by sediment entrainment, as they roll downhill like snowballs and magnify soil erosion. Careful control of drop conditions reveals two stable sandball morphologies: peanut-like shapes linked to hydrodynamic instabilities and toroidal forms that undergo mechanical locking from extreme sediment loading, which have potential implications for related problems in bioengineering, pharmaceuticals, and snow physics.